(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Current study was Based on the variables interact with each other to form a general framework of the pricing of banking services, and the role of profitability in the banking activity, because profit is the most important goal of commercial banks, that included the study United Bank, North Bank and Bank of Baghdad, and the each formation of bank were was collected about the prices (Iraqi dinar and the U.S. dollar) and interest percentages and then revenue (Iraqi Dinars) through banking channels, and each channel service included a group of well-known banking operations. The study found that the effect of prices, and interest on profitability and clear. There have been a correlation between the rates, and interest on profitability and the adoption of banks principle of competition in the pricing of services as well as the margin is as simple as it deems bank appropriate for some banking operations, as well as the number of services provided in Iraqi banks is very limited compared to banks world, and that the increase in these services and development for customers, they will to increase the profits of the bank. The study concludes with recommendations of the most notable is that the Iraqi banks attention to improving services and development, and increasing number, and the trend towards the development of competitive prices to attract customers, and achieve the satisfaction of existing customers, as well as attention to the pricing of banking services with the need for attention to the satisfaction of the customer on pricing during of service to him.